Cost-effectiveness of pediatric norovirus vaccination in daycare settings. Issue 15 (8th April 2021) - Steimle, Lauren N.; Havumaki, Joshua; Eisenberg, Marisa C.; Eisenberg, Joseph N.S.; Prosser, Lisa A.; Pike, Jamison; Ortega-Sanchez, Ismael R.; Mattison, Claire P.; Hall, Aron J.; Steele, Molly K.; Lopman, Benjamin A.; Hutton, David W.
Abstract: Objective: Noroviruses are the leading cause of acute gastroenteritis in the United States and outbreaks frequently occur in daycare settings. Results of norovirus vaccine trials have been promising, however there are open questions as to whether vaccination of daycare children would be cost-effective. We investigated the incremental cost-effectiveness of a hypothetical norovirus vaccination for children in daycare settings compared to no vaccination. Methods: We conducted a model-based cost-effectiveness analysis using a disease transmission model of children attending daycare. Vaccination with a 90% coverage rate in addition to the observed standard of care (exclusion of symptomatic children from daycare) was compared to the observed standard of care. The main outcomes measures were infections and deaths averted, quality-adjusted life years (QALYs), costs, and incremental cost-effectiveness ratio (ICER). Cost-effectiveness was analyzed from a societal perspective, including medical costs to children as well as productivity losses of parents, over a two-year time horizon. Data sources included outbreak surveillance data and published literature. Results: A 50% efficacious norovirus vaccine averts 571.83 norovirus cases and 0.003 norovirus-related deaths per 10, 000 children compared to the observed standard of care. A 200 norovirus vaccine that is 50% efficacious has a net cost increase of 178.10 per child and 0.025 more QALYs, resulting in an ICER of 7, 028/QALY. Based on the probabilistic sensitivity analysis, we estimated that a 200 vaccination with 50% efficacy was 94.0% likely to be cost-effective at a willingness-to-pay of 100, 000/QALY threshold and 95.3% likely at a 150, 000/QALY threshold. Conclusion: Due to the large disease burden associated with norovirus, it is likely that vaccinating children in daycares could be cost-effective, even with modest vaccine efficacy and a high per-child cost of vaccination. Norovirus vaccination of children in daycare has a cost-effectiveness ratio similar to other commonly recommended childhood vaccines.